"Academic innovation in service of" what? The scope of North American occupational science doctoral graduates' contributions from 1994–2015. Issue 2 (3rd April 2018) - Aldrich, Rebecca M.; Gupta, Jyothi; Rudman, Debbie Laliberte
ABSTRACT: More than 100 people have graduated with occupational science doctoral degrees in North America. Accordingly, there is a body of work that can be examined to assess what qualities have characterized doctoral-level occupational science inquiry to-date. In this preliminary study, we performed a directed content analysis of 101 dissertation abstracts published between 1994 and 2015 from four occupational science doctoral programs in the United States and Canada. Our analysis explored the extent to which the 101 doctoral studies, as evidenced by their abstracts, directly contributed to knowledge of occupation or humans as occupational beings. Our findings suggested that 40 studies made a direct contribution, 29 made an indirect contribution, and 32 made no contribution to the study of occupation or humans as occupational beings. Additional analyses revealed that studies in the direct and indirect categories relied heavily (80% and 69%, respectively) on qualitative methodologies, whereas studies in the no contribution category were more evenly split across qualitative (37%) and quantitative (47%) methodologies. A variety of topics and themes characterized studies in each category, and further research on 92 doctoral students' post-graduation publications showed that 50 made contributions to occupational science's knowledge base through published articles or book chapters. The findings from this preliminary inquiry provide a basis to critically reflect on the goals, outcomes, and functions of occupational science doctoral education as well as how the discipline has developed through doctoral work within evolving academic, scientific, and political landscapes.